Evaluation of bi-functional applications of ZnO nanoparticles prepared by green and chemical methods. Issue 6 (December 2019) - Kumar, M.R. Anil; Ravikumar, C.R.; Nagaswarupa, H.P.; Purshotam, B.; Gonfa, BedasaAbdisa; Murthy, H.C. Ananda; Sabir, Fedlu Kedir; Tadesse, Samson
Graphical abstract: Highlights: Green ZnO nanoparticles were synthesised by using the leaf extract of the plant Ruta Chalepensis . Photochemical and electrochemical properties of green ZnO (g-ZnO) NPs were compared with those of chemically synthesised ZnO (c-ZnO) NPs. g-ZnO NPs exhibited highest photocatalytic activity for Malachite Green (MG) dye. The superior electrochemical behavior was observed in the case of g-ZnO NPs. g-ZnO NPs exhibited higher electrode reversibility as observed from cyclic voltammetric studies. EIS studies also revealed lower charge capacitance for g-ZnO NPs. g-ZnO NPs can be considered as a better alternative photocatalyst for waste water treatment. Abstract: We report the chemical synthesis and green synthesis of zinc oxide nanoparticles (ZnO NPs) by using the leaf extract of the plant Ruta chalepensis . In addition, a comparative evaluation of photochemical and electrochemical properties of green ZnO (g-ZnO) and chemical ZnO (c-ZnO) NPs has been presented in this paper. The g-ZnO and c-ZnO NPs were found to exhibit uniform particle size distribution with an average diameter of 17.72 nm and 25.0 nm, respectively. These NPs possess hexagonal phase with wurtzite structure which is revealed by PXRD results. The SEM studies revealed a more uniform and flower like morphology for the g-ZnO NPs. The UV-DRS studies revealed the band energy gaps (Eg ) of 2.86 eV and 3.35 eV for g-ZnO and c-ZnO NPs, respectively. The degradation studies were carried out for three dyes, Malachite Blue (MB), Indigo Carmine (IC) and Malachite Green (MG). g-ZnO NPs exhibited highest photocatalytic activity for Malachite Green (MG) under UV light irradiation (from 0 to 60 min), when compared to c-ZnO NPs. Electrochemical studies have been carried out for both ZnO NPs in 1 M KOH solution. Cyclic voltammetric (CV) results showed higher electrode reversibility for g-ZnO NPs. The superior behavior observed for g-ZnO NPs can be attributed to its lower charge transfer resistance as confirmed by electrochemical impedance spectroscopy (EIS) study. The results also prove that g-ZnO NPs would be a better alternative photocatalyst for waste water treatment.